Preparation of Nutritious Ready-to-Drink Fruit and Vegetable Juice for Pregnant Women (4-6 months). - M. Abdallah, Hagir; A. Nanees, Raghad; F. Khatroush, Nosaiba; R. Altantani, Lamia; N. Smida , Fatema (Libyan Journal of Science &Technology, 2026)
Many pregnant women suffer from disorders during the primary period of preg nancy, which strongly influence the health of mothers and their embryos. This research aimed to prepare and estimate the chemical components of healthy and nutritious ready-to-drink juice prepared from fresh and dried fruits and vegetables known for their health benefits for pregnant women, such as avocado, banana, strawberry, raisins, dried figs, mint, green arugula and other natural ingredients. Three juice formulas were prepared with different natural ingredients, and the chemical composition was esti mated in terms of proximate analysis, quality characteristics, mineral content and en ergy content. Importantly, the percentage of carbohydrates in the samples ranged be tween 4.34 ±0.010 and 11.89±0.010. The results of the quality analysis indicated that the juice samples were characterized by moderate acidity (1.05±0.020, 4.34±0.00) and that the total soluble solids were within the limits stipulated for natural juices (12.50±0.200, 16.50±0.200). The energy content results demonstrated the high energy content of the formulas, which ranged between 58.84±0.14 and 101±0.26 kcal/100 ml. Mineral analysis revealed that the juice samples were rich in iron, zinc and copper, with values of 50.92±0.0, 5.21±0.428, and 2.21±0.013, respectively. This study confirmed that juice formulas provide a high energy content; important minerals such as iron and zinc; and an excellent percentage of fluids. The study recommended including this type of juice in pregnant women’s diets.